Kant and the law of war - Ripstein, Arthur (Oxford University Press, 2021)
The past two decades have seen renewed scholarly and popular interest in the law and morality of war. Positions that originated in the late Middle Ages through the 17th century have received more sophisticated philosophical elaboration. Although many contemporary writers draw on ideas that figure prominently in Kant's moral philosophy, his explicit discussions of war have not been brought into their proper place within these discussions and debates. Kant argues that a special morality governs the permissible use of force because of wars distinctive immorality. He characterizes war as barbaric, because in war might makes right - which side prevails does not depend on who is in the right. The very thing that makes war wrongful also provides the appropriate standard for evaluating the conduct of war, and the only basis for law governing war"--